"Even" conducting superiority in molecular wires designed by porphyrin and graphene nanoribbons. (April 2020) - Li, Jie; Li, Tao; Duan, Yunrui; Li, Hui
Abstract: Highly conducting molecular wires are extremely desirable in molecular-scale circuitry, but restricted by their role as tunnel barriers due to their steep conductance recession with the length. This work innovatively reveals that in equilibrium, the conductance of the newly designed porphyrin-graphene nanoribbons (GNRs) molecular wires would increase with the length, presenting appealing "even" conducting superiority, different with pure-GNRs molecular wires. Such anomalous transport behavior is not related with edge states of GNRs but the contribution of the porphyrin part in the transport. More interestingly, this "even" conducting advantage would be more prominent with slightly larger voltage, originated from narrower HOMO-LUMO gap of "even" assembled molecular wires. Besides, one of these hybrid molecular wires shows exceedingly strong transmission. This work suggests valuable applications of these new-assembled molecular wires in nano-electronics. Graphical abstract: Unlabelled Image Highlights: Porphyrin-GNRs molecular wires are innovatively designed. These wires show great potential in molecular-scale circuitry because of their unconventional conductance change with length. These wires present attractive "odd-even" conducting difference which would be more prominent with slightly larger voltage. The inner physical mechanisms of the conducting behavior are elucidated.